Experience and social support needs of becoming a mother on adolescent in Yogyakarta (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: The purpose of this study is to know the experience and social support need of becoming a mother on an adolescent.Method: This study is Qualitative research with descriptive phenomenology approach. Data collection was done by in-depth interview method and using the semi-structured study guide. The research was conducted at health center of Jetis, Gedong Tengen and Umbulharjo 1 in May - June 2017. The participants were 7 adolescents (18-19 years old) mothers who have 2 weeks - 12 months baby. The sampling was conducted by using purposive sampling and recorded by using a tape recorder. Data analysis was done manually by using Colaizzi method.Results: Five themes emerged from the results of data analysis: 1) variation of feelings experienced from pregnancy up to delivering the baby, 2) freedom from routine of baby care, 3) early experience of baby care, 4) social support from significant other and midwives, and 5) improved confidence in baby care.Conclusion: The variety of experiences by adolescent mothers is accompanied by social support providing increased confidence in caring for the baby